Low-grade fibromyxoid sarcoma of the parapharyngeal space: A case report and review of the literature - Corrado Toro; Paola Costa; Giada Maria Vecchio; Gaetano Magro (Oral and Maxillofacial Surgery Cases, 2020)
This paper reports a rare case of Low-grade ﬁbromyxoid sarcoma (LGFMS) that occurred primarily in the parapharyngeal space, in a 57-year-old woman. To the best of our knowledge, this is the first case of LGFMS arising from the parapharingeal space reported in the literature. Primary sarcomas of the head and neck region are very rare, accounting for approximately 1% of malignancies in this region. LGFMS is a distinctive type of soft-tissue sarcoma that was first described by Evans in 1987. LGFMS may be included in the differential diagnosis of tumors of the parapharyngeal space, and especially among the bland-looking spindle cell lesions. Despite its bland-looking morphology, this sarcoma should be recognized to avoid confusion with other bland-looking benign spindle cell lesions. Radical surgical resection with clear margins, is the treatment of choice of LGFMS. Despite its bland-looking histologic appearance, it is characterized by a malignant behavior with high rates of local recurrence and metastatic spread. For these reasones, all patients with LGFMS are recommended for long-term follow-up.